2019
DOI: 10.21767/2471-9803.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Raised CA125: a Cause for Concern?

Abstract: Cancer antigen 125 (also known as carbohydrate antigen 125 or CA 125) is an antigen first identified by Bast et al. Although much research has been done to understand the molecular structure of CA 125, its function remains a source of much speculation. At present, CA 125 is most commonly used in the diagnosis of epithelial non-mucinous ovarian cancers, and in monitoring their response to treatment. Following surgical resection, CA 125 levels are expected to half within 10 days and it is therefore a useful tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…CA-125, a mucin-type glycoprotein that is encoded by the MUC16 gene and associated with the cell membrane, is an imperfect biomarker for ovarian cancer due to shortcomings in sensitivity and specificity [ 7 ]. Elevated CA-125 levels can be observed in physiological (e.g., menstruation and pregnancy) and pathological conditions, particularly inflammatory diseases of the peritoneum including tuberculosis, endometriosis, pelvic inflammatory disease, adenomyosis, and peritoneal sarcoid [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA-125, a mucin-type glycoprotein that is encoded by the MUC16 gene and associated with the cell membrane, is an imperfect biomarker for ovarian cancer due to shortcomings in sensitivity and specificity [ 7 ]. Elevated CA-125 levels can be observed in physiological (e.g., menstruation and pregnancy) and pathological conditions, particularly inflammatory diseases of the peritoneum including tuberculosis, endometriosis, pelvic inflammatory disease, adenomyosis, and peritoneal sarcoid [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nongynecological conditions where CA 125 is raised are liver cirrhosis, pulmonary tuberculosis, interstitial lung disease, congestive heart failure, atrial fibrillation, and pericardial disease. 19 Two-dimensional or three-dimensional transvaginal ultrasound, transvaginal endoscopy, and transvaginal hydrolaparoscopy are helpful in early diagnosis and ablating endometriomas with a maximum diameter of 3 cm. 5 Laparoscopy, combined with the histopathological examination, is considered the gold standard for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…CA125 is a glycoprotein encoded by the mucin 16 (MUC16) genes detected by OC 125 monoclonal antibodies in cancerous ovarian tissues, which was first described by Bast et al in 1981 . Its upper limit is 35.0 U/mL in premenopausal and postmenopausal patients . Despite CA125 and its easy detection, certain disadvantages render this assay ineffective for the early screening of OC.…”
Section: Biomarkers For Ovarian Carcinomamentioning
confidence: 99%
“…37 Its upper limit is 35.0 U/mL in premenopausal and postmenopausal patients. 38 Despite CA125 and its easy detection, certain disadvantages render this assay ineffective for the early screening of OC. Its limitations are as follows: 39 (i) the specificity and positive predictive value of the test is comparatively greater in postmenopausal women than in premenopausal women because of the increased levels of CA125, also witnessed during other physiological conditions (like pregnancy, ovarian cysts, inflammatory peritoneal diseases, and endometriosis); (ii) CA125 was originally found to be elevated in serum among 82% of OC, but only 1% of healthy and 6% of benign controls; (iii) in several reports, only 50% to 60% of stage I OC patients and 75% to 90% of stage II OC patients have shown increased CA125 levels; and (iv) Dikmen et al 40 revealed the area under the curve (AUC: a graphical tool to compare markers and algorithms) for CA125 to be rather weak, hinting that CA125 is probably not very ideal for diagnosing OC.…”
Section: Biomarkers For Ovarian Carcinomamentioning
confidence: 99%